Réponses

2014-05-17T15:56:55+02:00
Bonjour,

Les inconnues sont a et b, on pose un système.
\begin{cases}0a+b = -7\\ 3a+b = -52\end{cases}\\
\begin{cases}b= -7\\ 3a-7 = -52\end{cases}\\
\begin{cases}b= -7\\ 3a = -45\end{cases}\\
\begin{cases}b= -7\\ a = -15\end{cases}\\

On a donc h(x) = -15x-7.

Si tu as des questions, n'hésite pas ! =)
2014-05-17T15:57:38+02:00
H(0) = -7
h(3) = -52

h(x) = ax+b

Donc,

h(0) = 0x + (-7) --> b = -7
h(3) = 3x - 7 = -52
<=> 3x = -45
<=> x = -15

D'où h(x) = -15x - 7